General banking system of Mutual Trust Bank Limited, Mohammadpur Branch - Rahman, Mohammed Mushfiqur (Brac University, 2023)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2022.